Incident of Mucositis and The Factors that Influence it on Children with Cancer Who Received Chemotherapy - Sri Hendrawati; Ikeu Nurhidayah; Henny Suzana Mediani; Ai Mardhiyah (Jurnal Keperawatan, 2019)
Chemotherapy shows high effectiveness, but also has side effects, including mucositis. Mucositis can cause pain, difficulty sleeping, eating disorders, mood, and activity, which has implications for the quality of life of children. The purpose of this study was to identify the incidence of mucositis and the factors that influence the incidence of mucositis in cancerous children receiving chemotherapy treatment. This research method is descriptive correlational analysis with cross sectional design. Consecutive sampling technique was used to establish respondents as research samples so as to get 60 respondents. Data were analyzed univariately and bivariately. Bivariate analysis was performed with Chi square test and 2 mean difference test to see differences in the mean values of mucositis before and after chemotherapy. The results showed that almost all cancer children who received chemotherapy had 53 people (88.3%) and a small portion, 7 people (11.7%) had no mucositis. There was a significant difference in the mean value (p = 0,000) between before and after chemotherapy with an increase in the average mucositis value of 3.12. The research shows that there is a significant relationship (p <0.05) between previous mucositis experience (p = 0,000), type of cancer (p = 0.025), type of chemotherapy (p = 0.010), and duration of therapy (p = 0.027) and the incidence of mucositis. Meanwhile nutritional status was not related to the incidence of mucositis (p = 0.077). Nurses, as health workers who most often contact with patients, should be able to improve nursing care in cancer children who get chemotherapy in minimizing the occurrence of mucositis by conducting routine mucositis and oral care assessments.